2022
DOI: 10.21775/cimb.042.097
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Genetics of Borrelia

Abstract: The genus Borrelia consists of evolutionarily and genetically diverse bacterial species that cause a variety of diseases in humans and domestic animals. These vector-borne spirochetes can be classified into two major evolutionary groups, the Lyme borreliosis clade and the relapsing fever clade, both of which have complex transmission cycles during which they interact with multiple host species and arthropod vectors. Molecular, ecological, and evolutionary studies have each provided significant contributions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 135 publications
(228 reference statements)
0
8
0
Order By: Relevance
“…In addition, competition experiments between B. afzelii strains showed that strain interaction affects bacterial density and prevalence in immature I. ricinus ticks ( Genné et al., 2018 ). Considering that B. burgdorferi density within ticks positively correlates with the probability of transmission to vertebrate hosts ( Rego et al., 2014 ), it is expected that competition among co-infecting strains may reduce the evolutionary fitness of the subdominant strain ( Oppler et al, 2021 ). Competition among co-infecting strains could select for traits to suppress the growth of other strains or to escape suppression.…”
Section: Co-infections With Strains Of the Same Pathogen Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, competition experiments between B. afzelii strains showed that strain interaction affects bacterial density and prevalence in immature I. ricinus ticks ( Genné et al., 2018 ). Considering that B. burgdorferi density within ticks positively correlates with the probability of transmission to vertebrate hosts ( Rego et al., 2014 ), it is expected that competition among co-infecting strains may reduce the evolutionary fitness of the subdominant strain ( Oppler et al, 2021 ). Competition among co-infecting strains could select for traits to suppress the growth of other strains or to escape suppression.…”
Section: Co-infections With Strains Of the Same Pathogen Speciesmentioning
confidence: 99%
“…Competition among co-infecting strains could select for traits to suppress the growth of other strains or to escape suppression. However, there is no evidence that such traits have evolved in Borrelia and the evolutionary pressures that may produce them are currently unknown ( Oppler et al, 2021 ). Future research could investigate experimentally the selective pressures created by competition between co-infecting Borrelia strains and determine their relative evolutionary outcomes.…”
Section: Co-infections With Strains Of the Same Pathogen Speciesmentioning
confidence: 99%
“…Pathogenic species of the genus Borrelia are zoonotic bacteria that cause emerging and re-emerging infectious diseases worldwide and constitute a major threat to public health [1]. This genus is composed of two welldefined monophyletic groups: the Borrelia burgdorferi sensu lato (Bb) complex, which cause Lyme borreliosis and are transmitted by hard ticks of the genus Ixodes, and borreliae of the relapsing fever (RF) group, transmitted mainly by soft ticks of the genus Ornithodoros, some species by ixodid ticks (e.g., Borrelia miyamotoi), and Borrelia recurrentis, transmitted by the clothing louse [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most species of Borrelia have complex transmission cycles interacting with multiple vertebrate hosts and vector ticks [1]. For instance, several members of the order Rodentia are reservoir hosts [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…We refer to pathogenic Borreliella species collectively as the LD spirochetes. LD spirochetes are maintained in nature in an enzootic cycle involving Ixodes species ticks and diverse vertebrate reservoirs ( 5 , 6 ). The CDC reported in 2016 that Ixodes scapularis and Ixodes pacificus ticks, the primary vectors for LD in North America, are present in 49.2% of United States counties ( 7 ).…”
Section: Introductionmentioning
confidence: 99%